Bayesian Self‐Optimization for Telescoped Continuous Flow Synthesis. Issue 3 (13th December 2022) - Clayton, Adam D.; Pyzer‐Knapp, Edward O.; Purdie, Mark; Jones, Martin F.; Barthelme, Alexandre; Pavey, John; Kapur, Nikil; Chamberlain, Thomas W.; Blacker, A. John; Bourne, Richard A.
Abstract: The optimization of multistep chemical syntheses is critical for the rapid development of new pharmaceuticals. However, concatenating individually optimized reactions can lead to inefficient multistep syntheses, owing to chemical interdependencies between the steps. Herein, we develop an automated continuous flow platform for the simultaneous optimization of telescoped reactions. Our approach is applied to a Heck cyclization‐deprotection reaction sequence, used in the synthesis of a precursor for 1‐methyltetrahydroisoquinoline C5 functionalization. A simple method for multipoint sampling with a single online HPLC instrument was designed, enabling accurate quantification of each reaction, and an in‐depth understanding of the reaction pathways. Notably, integration of Bayesian optimization techniques identified an 81 % overall yield in just 14 h, and revealed a favorable competing pathway for formation of the desired product. Abstract : An autonomous continuous flow platform for the rapid development of multistep synthetic pathways is reported. New multipoint sampling and Bayesian optimization techniques were combined, enabling simultaneous identification of optimum reaction conditions within a pharmaceutical process. The short optimization times achieved are promising for development of telescoped reactions in the future.